2024
DOI: 10.1002/ohn.671
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation for Treatment of Tinnitus: A Systematic Review and Meta‐Analysis

Luke D. Heiland,
Johnny M. Owen,
Shaun A. Nguyen
et al.

Abstract: ObjectiveTo evaluate the treatment efficacy of neuromodulation versus sham for the treatment of tinnitus.Data SourcesCochrane Library, CINAHL, PubMed, Scopus.Review MethodsThe Cochrane Library, CINAHL, PubMed, and Scopus were searched from inception through May 2023 for English language articles documenting “neuromodulation” and “tinnitus” stratified by sham‐controlled randomized control trials with 40 or more patients. Data collected included Beck Anxiety Inventory, Beck Depression Inventory (BDI), Tinnitus H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…There was no significant difference in the age, sex, threshold of PTA, initial THI, VAS score, and BDI among the three groups. Twenty-one patients were considered to have borderline clinical depression (score of [17][18][19][20] or moderate depression (score of 21-30) based on their BDI score.…”
Section: Demographic Data Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no significant difference in the age, sex, threshold of PTA, initial THI, VAS score, and BDI among the three groups. Twenty-one patients were considered to have borderline clinical depression (score of [17][18][19][20] or moderate depression (score of 21-30) based on their BDI score.…”
Section: Demographic Data Of Patientsmentioning
confidence: 99%
“…The targets to be stimulated through tDCS in tinnitus are mainly the auditory cortex [ 14 , 15 ], dorsolateral prefrontal cortex (DLPFC) [ 16 , 17 ], and left temporoparietal area (LTPA) [ 18 ], which are different for each study. Most studies reported significant improvement in patients who have tinnitus with tDCS treatment, but the duration of tinnitus suppression varies from minutes to several days [ 19 , 20 , 21 ]. Additionally, studies to date have conducted tDCS on chronic subjective tinnitus, but the subjects’ loudness, distress of tinnitus, level of hearing threshold, and psychiatric comorbidity have varied, and there is no report on whether there is an effect of suppressing tinnitus through stimulation several times a day.…”
Section: Introductionmentioning
confidence: 99%